2012
DOI: 10.1128/aem.06585-11
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Growth Strategies of Soil Bacteria as Revealed by Large-Scale Colony Tracking

Abstract: Our understanding of microbial ecology has been significantly furthered in recent years by advances in sequencing techniques, but comprehensive surveys of the phenotypic characteristics of environmental bacteria remain rare. Such phenotypic data are crucial for understanding the microbial strategies for growth and the diversity of microbial ecosystems. Here, we describe a high-throughput measurement of the growth of thousands of bacterial colonies using an array of flat-bed scanners coupled with automated imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 65 publications
3
42
0
Order By: Relevance
“…This view contrasts with empirical surveys of natural bacterial communities, which suggest that competitive interactions predominate over cooperative interactions (31). However, it has also been suggested that cooperation between different genotypes may explain the unculturability of many species in the laboratory when in monoculture (32)(33)(34). If correct, studies with culturable species could underestimate cooperativity in microbial communities.…”
mentioning
confidence: 85%
“…This view contrasts with empirical surveys of natural bacterial communities, which suggest that competitive interactions predominate over cooperative interactions (31). However, it has also been suggested that cooperation between different genotypes may explain the unculturability of many species in the laboratory when in monoculture (32)(33)(34). If correct, studies with culturable species could underestimate cooperativity in microbial communities.…”
mentioning
confidence: 85%
“…Beneficiary microbes dependent on diffusible products produced by helpers appear to be very widespread in nature. For instance, most microcolonies from a soil community developed more quickly when other community members were growing nearby [9]. Many previously unculturable bacteria have been induced to grow in the laboratory using coculture either with mixed natural communities [10] or with specific helper microbes [6,8,11].…”
mentioning
confidence: 99%
“…Additionally, it can report metrics characterizing color, 72 shape and proximity of neighboring colonies. We speculate that ColTapp will prove useful in a broad 73 spectrum of microbiology applications, such as species identification in environmental samples as 74 shown by Ernebjerg & Kishony (2012). 75…”
Section: Introduction 33mentioning
confidence: 96%